Family Communication Conflict Representation in Dua Hati Biru: A Semiotic Analysis Based on Roland Barthes - Yughni Faidah; Faridah (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
This study analyzes the representation of family communication conflict in the film Dua Hati Biru using Roland Barthes' semiotic approach. The film Dua Hati Biru was chosen as the object of research because it displays various realistic family conflict dynamics, especially between parents and children. This study uses a descriptive qualitative method with semiotic analysis techniques. Through Roland Barthes' semiotic analysis, this study identifies the meaning of denotation, connotation, and myth in various scenes that depict family conflict. The results of the study indicate that the conflict that occurs in this film can be categorized into solvable conflict and perpetual conflict. The findings of this study reveal that communication conflict in the family is not only influenced by differences of opinion, but also by cultural factors and social structures that are inherited between generations. This study also explains the Islamic perspective as a way to overcome family communication conflict, namely through deliberation and good communication. Thus, a deeper understanding of the representation of communication conflict in the media, such as films, can provide insight for the community in resolving family conflicts more effectively.